Investigating the Passengers’ Attitude to the Quality of Rolling Stock in the Moscow Underground Using N. Kano Methodology - I. V. Lopatinskaya; N. I. Ivashkova (Вестник Российского экономического университета имени Г. В. Плеханова)
The goal of the present research is to assess the quality of rolling stock used by transport operators and to prepare a set of recommendations dealing with its revision. The rolling stock refers to the so-called technical quality of the service. It is the technical quality which is a key product offered to the customer. The authors give a brief review of Kano methodology and put forward the authors' adaptation of the methodology and classification of rolling stock attributes and their impact on passengers' satisfaction. Findings of the field research dealing with perception of the rolling stock quality in the Moscow underground are provided. The key result is classification of rolling stock attributes using Kano methodology and finding their importance for passengers. The article also formulates recommendations on arranging new rolling stock of the Moscow underground, including five strategies of introduction with regard to attributes' importance.